Genomic signatures of selection in bats surviving white‐nose syndrome. Issue 22 (8th February 2021) - Gignoux‐Wolfsohn, Sarah A.; Pinsky, Malin L.; Kerwin, Kathleen; Herzog, Carl; Hall, MacKenzie; Bennett, Alyssa B.; Fefferman, Nina H.; Maslo, Brooke
Abstract: Rapid evolution of advantageous traits following abrupt environmental change can help populations recover from demographic decline. However, for many introduced diseases affecting longer‐lived, slower reproducing hosts, mortality is likely to outpace the acquisition of adaptive de novo mutations. Adaptive alleles must therefore be selected from standing genetic variation, a process that leaves few detectable genomic signatures. Here, we present whole genome evidence for selection in bat populations that are recovering from white‐nose syndrome (WNS). We collected samples both during and after a WNS‐induced mass mortality event in two little brown bat populations that are beginning to show signs of recovery and found signatures of soft sweeps from standing genetic variation at multiple loci throughout the genome. We identified one locus putatively under selection in a gene associated with the immune system. Multiple loci putatively under selection were located within genes previously linked to host response to WNS as well as to changes in metabolism during hibernation. Results from two additional populations suggested that loci under selection may differ somewhat among populations. Through these findings, we suggest that WNS‐induced selection may contribute to genetic resistance in this slowly reproducing species threatened with extinction. Abstract : see also the Perspective by Christopher P. Kozakiewicz and W. Chris Funk.